2018
DOI: 10.1016/j.hpb.2018.06.2432
|View full text |Cite
|
Sign up to set email alerts
|

Geographic disparities limit access to liver transplantation

Abstract: Background: Piggy-back (PB) anastomosis with implantation on the common trunk is the standard technique for patients undergoing whole graft liver transplantation with caval preservation. While piggy back anastomosis with right hepatic vein (RHV-PB) implantation allows decreasing the risk of caval twisting in case of partial graft liver transplantation, its value in patients receiving small sized whole liver grafts and large hepatic fossa, remains poorly described. Methods: From 2010 to 2016, all patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Once referred, however, rural residents were 14% less likely to be waitlisted for LT (risk ratio = 0.86; 95% CI, 0.83-0.89) and 20% less likely to receive a transplant (risk ratio = 0.80; 95% CI, 0.77-0.84) when compared to urban residents in a cohort study from an older era (1999)(2000)(2001)(2002)(2003)(2004)). [8] More recent single-center data showed that urban compared to rural residents had 33% higher odds of LT. [9] Importantly, thus far, studies have not shown any significant differences in outcomes after transplant between the 2 groups. [8,9] The clear gap in data means lower investment in the problem: more robust and up-to-date studies on transplant outcomes across the rural-urban continuum, including pre/post-Acuity Circle implementation, are needed as a call to action.…”
Section: Current Status Of Lt In Rural Americamentioning
confidence: 91%
See 4 more Smart Citations
“…Once referred, however, rural residents were 14% less likely to be waitlisted for LT (risk ratio = 0.86; 95% CI, 0.83-0.89) and 20% less likely to receive a transplant (risk ratio = 0.80; 95% CI, 0.77-0.84) when compared to urban residents in a cohort study from an older era (1999)(2000)(2001)(2002)(2003)(2004)). [8] More recent single-center data showed that urban compared to rural residents had 33% higher odds of LT. [9] Importantly, thus far, studies have not shown any significant differences in outcomes after transplant between the 2 groups. [8,9] The clear gap in data means lower investment in the problem: more robust and up-to-date studies on transplant outcomes across the rural-urban continuum, including pre/post-Acuity Circle implementation, are needed as a call to action.…”
Section: Current Status Of Lt In Rural Americamentioning
confidence: 91%
“…Once referred, however, rural residents were 14% less likely to be waitlisted for LT (risk ratio=0.86; 95% CI, 0.83–0.89) and 20% less likely to receive a transplant (risk ratio=0.80; 95% CI, 0.77–0.84) when compared to urban residents in a cohort study from an older era (1999–2004) 8 . More recent single-center data showed that urban compared to rural residents had 33% higher odds of LT 9 . Importantly, thus far, studies have not shown any significant differences in outcomes after transplant between the 2 groups 8,9 .…”
Section: Current Status Of Lt In Rural Americamentioning
confidence: 99%
See 3 more Smart Citations